2020
DOI: 10.1016/j.jbo.2020.100327
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic value of circulating miRNA for multiple myeloma: A meta-analysis

Abstract: Highlights This meta-analysis is a comprehensively studies of microRNA in MM. MicroRNA clusters helped to distinguish MM and healthy people. MicroRNA is a potential noninvasive biomarker in early diagnosis of MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…We updated this meta-analysis to figure out whether the circulating miRNAs could be promising means for early detection of MM with the latest evidence. The pooled sensitivity, specificity, AUC, PLR, NLR, and DOR were 0.79, 0.86, 0.87, 5, 0.27, and 22, respectively, consistent with the previous meta-analysis (10). Summary LRP and LRN for Index Test suggest a small number of studies have relatively high value for diagnosis conformation and/or exclusion.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We updated this meta-analysis to figure out whether the circulating miRNAs could be promising means for early detection of MM with the latest evidence. The pooled sensitivity, specificity, AUC, PLR, NLR, and DOR were 0.79, 0.86, 0.87, 5, 0.27, and 22, respectively, consistent with the previous meta-analysis (10). Summary LRP and LRN for Index Test suggest a small number of studies have relatively high value for diagnosis conformation and/or exclusion.…”
Section: Discussionsupporting
confidence: 87%
“…However, the quality assessment of literatures presents a few ignorable flaws and uncertainties, which are somewhat inconsistent with the results of the previous meta-analysis (10), possibly because of the different versions of evaluation tools or the strictness in our assessment. We found that some of the literatures did not specify the study design, patient information (stage/Ig isotype/treatment information), or the time interval between the reference standard and miRNA detection.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations